Impact of rifampicin on the pharmacokinetics of clarithromycin and 14-hydroxy clarithromycin in patients with multidrug combination therapy for pulmonary Mycobacterium avium complex infection. Issue 1 (January 2022) - Iketani, Osamu; Komeya, Akari; Enoki, Yuki; Taguchi, Kazuaki; Uno, Shunsuke; Uwamino, Yoshifumi; Matsumoto, Kazuaki; Kizu, Junko; Hasegawa, Naoki
Abstract: Introduction: Clarithromycin (CAM), ethambutol (EB), and rifampicin (RFP) combination therapy is used to treat pulmonary Mycobacterium avium complex (MAC) infection; however, serum CAM concentration decreases due to RFP-mediated induction of CYP3A activity. Therefore, we investigated the pharmacokinetics of CAM, 14-hydroxy clarithromycin (14-OH CAM), EB, and RFP in patients receiving this three-drug combination therapy. Methods: CAM monotherapy was started, EB was added 2 weeks later, and RFP was added 2 weeks after that. Serum CAM, 14-OH CAM, EB, and RFP concentrations were measured before and at 2, 4, 6, and 12 or 24 h after administration on days 14, 28, and 42, and pharmacokinetic parameters were calculated. Results: Median area under the curve (AUC) of CAM decreased by 92.1% from 0 to 12 h after concomitant administration of RFP compared with CAM monotherapy [1.7 (interquartile range [IQR], 1.4–1.8) μg·h/mL vs. 21.5 (IQR, 17.7–32.3) μg·h/mL, respectively]. In contrast, median AUC of 14-OH CAM was not significantly different between concomitant administration of RFP [9.1 (IQR, 7.9–10.9) μg·h/mL] and CAM monotherapy [8.2 (IQR, 6.3–9.3) μg·h/mL]. AUCs of CAM and 14-OH CAM did not change in CAM+EB combination therapy. Conclusions: When RFP is combined with CAM in the treatment of pulmonary MAC infection, the blood concentration of CAM significantly decreased and that of the active metabolite 14-OH CAM increased, but not significantly. Our results suggest that combination therapy with CAM and RFP needs to be reconsidered and may require dose modification in the treatment of pulmonary MAC infection.